A prospective study of health‐related quality of life of boys with severe haemophilia A in China: comparing on‐demand to prophylaxis treatment. Issue 3 (27th March 2017) - Wu, R.; Sun, J.; Xiao, J.; Liu, Y.; Xue, F.; Wang, H.; Tang, L.; Zhao, Y.; Li, K.; Yang, R.; Hu, Y.; Luke, K.‐H.; et al.
Abstract : Introduction: Treatment for boys with haemophilia in China is rapidly improving; however, comprehensive outcomes have not been examined prospectively. Aim: The aim of this study was to evaluate the effect of short‐term full‐dose prophylaxis compared to on‐demand treatment, on the Health‐Related Quality of Life (HR‐QoL) of boys with severe haemophilia A (HA) in China. Methods: Boys with severe HA (FVIII<1%) completed 3 months of on‐demand treatment and 3 months of full‐dose prophylaxis (25 FVIII IU per kg 3x per week). The primary outcomes were child‐ and parent‐reported Canadian Hemophilia Outcomes – Kids Life Assessment Tool (CHO‐KLAT) scores. The number and type of bleeds and Activities Scale for Kids (ASK) scores were also recorded. Results: Analyses included 23 boys between 4 and 15.9 years of age. The number of bleeds decreased by 94% on prophylaxis ( P < 0.0001, Wilcoxon Signed‐Rank test). The mean child‐reported CHO‐KLAT scores for boys ≥7 years (n = 20) was 61.4 (±10.9) during on‐demand treatment and 61.9 (±11.4) following short‐term prophylaxis ( P = 0.72, paired t‐test). The mean parent‐reported CHO‐KLAT score during the on‐demand phase was 54.4 (±10.5) with an increase of 3.8 points (±8.1; P = 0.04, paired t‐test) following prophylaxis. Conclusions: Child‐reported CHO‐KLAT scores were lower in boys with severe HA in China than reported in countries with access to full‐dose prophylaxis. Boys reported higher HR‐QoL scores than their parents. Small improvements in ASK scores were noted following the prophylaxis phase. These changes were only significant in the parent‐reported CHO‐KLAT scores. Longer term prospective clinical trials are needed in China to determine the impact of prophylaxis on HR‐QoL in boys with severe HA.